Novel Fluorescent Mitochondria-Targeted Probe MitoCLox Reports Lipid Peroxidation in Response to Oxidative Stress In Vivo. (10th February 2020) - Lyamzaev, Konstantin G.; Panteleeva, Alisa A.; Karpukhina, Anna A.; Galkin, Ivan I.; Popova, Ekatherina N.; Pletjushkina, Olga Yu.; Rieger, Bettina; Busch, Karin B.; Mulkidjanian, Armen Y.; Chernyak, Boris V.
Abstract : A new mitochondria-targeted probe MitoCLox was designed as a starting compound for a series of probes sensitive to cardiolipin (CL) peroxidation. Fluorescence microscopy reported selective accumulation of MitoCLox in mitochondria of diverse living cell cultures and its oxidation under stress conditions, particularly those known to cause a selective cardiolipin oxidation. Ratiometric fluorescence measurements using flow cytometry showed a remarkable dependence of the MitoCLox dynamic range on the oxidation of the sample. Specifically, MitoCLox oxidation was induced by low doses of hydrogen peroxide or organic hydroperoxide. The mitochondria-targeted antioxidant 10-(6 ′ -plastoquinonyl)decyltriphenyl-phosphonium (SkQ1), which was shown earlier to selectively protect cardiolipin from oxidation, prevented hydrogen peroxide-induced MitoCLox oxidation in the cells. Concurrent tracing of MitoCLox oxidation and membrane potential changes in response to hydrogen peroxide addition showed that the oxidation of MitoCLox started without a delay and was complete during the first hour, whereas the membrane potential started to decay after 40 minutes of incubation. Hence, MitoCLox could be used for splitting the cell response to oxidative stress into separate steps. Application of MitoCLox revealed heterogeneity of the mitochondrial population; in living endothelial cells, a fraction of small, rounded mitochondria with an increased level of lipid peroxidation were detected near the nucleus. In addition, the MitoCLox staining revealed a specific fraction of cells with an increased level of oxidized lipids also in the culture of human myoblasts. The fraction of such cells increased in high-density cultures. These specific conditions correspond to the initiation of spontaneous myogenesis in vitro, which indicates that oxidation may precede the onset of myogenic differentiation. These data point to a possible participation of oxidized CL in cell signalling and differentiation.